THE IMPACT OF ARTIFICIAL INTELLIGENCE ON EDUCATION - Elomonova Mahliyo (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Artificial Intelligence (AI) is transforming the field of education by introducing innovative solutions that enhance learning experiences, streamline administrative tasks, and improve global access to quality education. This article examines the profound impact of AI on education, focusing on key areas such as personalized learning, administrative efficiency, and accessibility. AI-powered tools adapt learning processes to individual needs, making education more engaging and effective, while automation reduces the workload of educators, enabling them to focus on teaching. However, challenges such as high implementation costs, data privacy concerns, and resistance from educators hinder its widespread adoption. The article also explores the future prospects of AI in education, including the integration of virtual reality, early detection of learning disabilities, and support for lifelong learning. By addressing existing challenges, AI has the potential to create a more inclusive and innovative educational environment.